Towards an intersectional literary criticism: Cross-Identity representations, social location, and Shani Mootoo's intervention. Issue 2 (4th March 2023) - MacDonald, Geoffrey
ABSTRACT: This article explores how literary critics can approach cross-identity representations in a way that addresses the complex use of alterity by authors who re/construct pluralistic societies and are also marginalized by the colonial matrix of power. Recent theorists such as Mark Bracher have noted that social justice is as imperative to literary scholarship as the late 20th- to early 21st- century aesthetic turn (identified by Ruth Gilligan) that decried an overemphasis on political readings. It is argued here that literary criticism should use an intersectional approach. Key elements of intersectionality, as articulated by Sirma Bilge and Patricia Hill Collins, are applied to literary study and in particular to Shani Mootoo's Moving Forward Sideways Like a Crab . Such a framework makes the question of "good" and "bad" representations irrelevant and uses authorial identity as but one piece of a larger literary approach that honours the complexity of literature alongside undeniable power dynamics.